Research on the coupling coordinated development evaluation of China’s provincial technological innovation and financial support based on KGM-MOP - Yang, Qing; Cao, Lanjuan; Wang, Xiaohua; Wu, Xiangrong; Guo, Xiuhui (Frontiers in Environmental Science, 2022)
Technology finance is an important means to support technological innovation, the development level of which is one of the key points of innovation driven strategy in the new era. Based on the correlation-variation coefficient method, we screen the indicators of various provinces in China, analyze the indicator adaptation relationship for the data of 30 provinces from 2011 to 2020, carry out empirical research on technology finance by using the coupling coordinated development evaluation, and use KGM (1, n) grey prediction and NSGA-III objective optimization method to determine the trend of coupling coordinated development of each region. The research shows that the indicators of technology finance are industry-oriented, the level of integration of technology and finance across the country is different, to be specific, the East is on the high side, the central part is steady with some opportunities, the West has room for improvement and the Northeast has obvious weaknesses, and the driving force of the coupling coordinated development of technology and finance is limited in sustainability, etc. We propose to strengthen the top-level design and supervision of technology finance, implement accurate measures according to local conditions, and adopt the regional linkage and mutual assistance development mode to help regional efficient and coordinated development.